RSS'S Tryst with Politics : From Hedgewar to Sudarshan - Kanungo, Pralay, (Brill | Manohar Publishers & Distributors, 2024)
This RSS is perhaps the most controversial organization in con-temporary India. This book explores the mission, method and motive of the RSS and suggests that the ideological core of the RSS-Hindu Rashtra-is political and not cultural. It argues that K.B. Hedgewar, the founder of the RSS, had a clear political mission, while M.S. Golwalkar, his successor, despite his saintly appearance and overt distaste for 'politics', sharpened and amplified its ideology. Nevertheless, deep down the RSS remained political. This book goes on to delineate how Balasaheb Deoras, the third chief, who did not have much of a fancy for 'culture', plunged into Indian politics on the organizational and ideological foundation created by his predecessors. Deoras seriously pursued the homogenizing agenda of the RSS to integrate different sections like the Dalits, tribals and women into the fold of the Hindu Rashtra. Rajendra Singh the sucessor of Deoras, consolidated the political mission by getting control over the State and reaching out to civil society more effectively. K.S. Sudarshan, the present chief, while attempting to retain a tight control over State power, simultaneously reinforces Hindutva. The author concludes by arguing that the RSS-from Hedgewar to Sudarshan-continues its tryst with politics to convert India into a Hindu Rashtra. Highly readable and of contemporary relevance, this book would be of immense interest to political scientists, political sociologists and all those interested in present-day India.